Writing Skills Teaching Methods for Elementary School Students: Scramble in Connecting Arabic Letters - Huda, Nurul; Isnaini Maulidia Annisa,; Muhammad Nuruzzaman Syam, (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2024)
This study aims to understand how the scramble method is implemented in connecting Arabic letters in teaching writing skills (maharatul kitabah) to elementary school students, and to identify the supporting and inhibiting factors. This research is qualitative and uses a field research approach. The data sources are Arabic language teachers and third-grade students from MI Al-Hidayah Mangli Jember. Data collection methods include observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and conclusion drawing. The results show that the implementation of the scramble method in connecting Arabic letters in maharatul kitabah learning involves three stages: planning, execution, and evaluation. The supporting factors for implementing the scramble method include student enthusiasm and motivation, the presence of engaging game elements, heterogeneous group division, and the provision of rewards. Meanwhile, the inhibiting factors include the teacher's limited understanding of student conditions, differences in student learning abilities, and limited time allocation. These findings can serve as a reference for Arabic language practitioners in exploring appropriate methods for teaching Arabic.